2021
DOI: 10.3389/fgene.2021.720081
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Assessment of Runs of Homozygosity and Estimates of Genomic Inbreeding in a Chinese Composite Pig Breed

Abstract: The primary purpose of the current study was to assess the genetic diversity, runs of homozygosity (ROH) and ROH islands in a Chinese composite pig and explore hotspot regions for traces of selection. First, we estimated the length, number, and frequency of ROH in 262 Xidu black pigs using the Porcine SNP50 BeadChip and compared the estimates of inbreeding coefficients, which were calculated based on ROHs (FROH) and homozygosity (FHOM). Our result shows that a total of 7,248 ROH exceeding 1Mb were detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The Xidu black pig is a composite breed, with about 50% Hubei white, 25% Meishan, and 25% Enshi black pig inheritance ( 17 ). It has good meat quality, making it a good subject for this study ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Xidu black pig is a composite breed, with about 50% Hubei white, 25% Meishan, and 25% Enshi black pig inheritance ( 17 ). It has good meat quality, making it a good subject for this study ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of this study is to investigate the population structure and genetic diversity so as to provide better conservation strategies for TC pigs. Numerous studies have shown that multi-dimensional scaling (MDS) and phylogenetic tree analyses are effective methods for the investigation of population structure, that the proportion of polymorphic loci (P N ), minor allele frequency (MAF), heterozygosity, and nucleotide diversity (Pi) in combination with linkage disequilibrium (LD) and effective population size (Ne) levels are good indicators reflecting the genetic diversity of the population, and that runs of homozygosity (ROH) and ROH island analyses can reveal the inbreeding of the genome ( Cai et al, 2020 ; Xu et al, 2021 ). Owing to the rapid development of molecular biology in recent years, a variety of markers and DNA sequences of different species can be determined easily at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The following criteria and thresholds were used to define the ROH: a sliding window of 50 SNPs, a maximum missingness of 1 allele, a minimum length of 25,000 bp, at least 30 homozygous SNPs included in the ROH, a minimum density of 1 SNP per 1000 kilobases, and a minimum length of 1 Mb. The algorithm of ROH is extensively described by Xu et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%